Relationship between higher intra-amniotic pressures in polyhydramnios and maternal symptoms. (April 2019) - Katsura, Daisuke; Takahashi, Yuichiro; Iwagaki, Shigenori; Chiaki, Rika; Asai, Kazuhiko; Koike, Masako; Yasumi, Shunsuke; Furuhashi, Madoka; Murakami, Takashi
Abstract: Objectives: Our study aimed to analyze the differences in intra-amniotic pressures in patients with polyhydramnios with and without symptoms. Study design: We recruited patients with pregnancies in which amnioreduction was performed for polyhydramnios in the Department of Fetal-Maternal Medicine at Nagara Medical Center between April 2017 and August 2018. Amnioreduction was performed for severe polyhydramnios with maternal symptoms [symptomatic group] or polyhydramnios without maternal symptoms [asymptomatic group] such as abdominal distension, dyspnea, or threatened premature labor. We measured the intra-amniotic pressure after every 200 ml volume reduction during the amnioreduction. Results: A total of 27 patients who underwent amnioreduction were classified into symptomatic (66.7%, 18/27) and asymptomatic (33.3%, 9/27) groups. Gestational age, amniotic fluid index at the time of amnioreduction, and the volume of amniotic fluid removed were not significantly different between the symptomatic and asymptomatic groups [median 32.4 weeks vs. 33.1 weeks, median 38.0 cm vs. 39.0 cm, and median 1500 ml vs. 2500 ml, respectively]. However; the intra-amniotic pressure before amnioreduction was significantly higher in the symptomatic group than in the asymptomatic group [median 15.0 mmHg (range, 10–27) vs. 10.0 mmHg (range, 6.0–13); p < 0.005]. After amnioreduction, these pressures decreased significantly to median 9.0 mmHg (range, 5.0–13) (p < 0.001) in the symptomatic and 7.0 mmHg (range, 4.0–11) (p < 0.05) in the asymptomatic group. The median intra-amniotic pressure gradually decreased and reached a plateau during the amnioreductions in both groups. Conclusions: With polyhydramnios, the intra-amniotic pressure was significantly higher in the symptomatic group than in the asymptomatic group. Therefore, uterine pressure tolerance might vary according to the individual. In addition, intra-amniotic pressure monitoring might enhance the safety during amnioreduction procedures to avoid drastic and potentially harmful pressure changes.